Determining the performance of lignin-based flocculants in improving biosludge dewaterability. (1st January 2023) - Ghazisaidi, Hamed; Wang, Vincent; Fatehi, Pedram; Tran, Honghi; Meyer, Torsten; Allen, D. Grant
Abstract: In the wastewater treatment plant of pulp and paper mills, biosludge dewatering is needed to reduce the sludge handling and disposal costs. It is usually facilitated by means of the addition of synthetic polymers. There is increasing interest in replacing synthetic polymers with biopolymers derived from low value by-products or industrial residuals to improve the environmental footprint of dewatering. In this study, lignin-based flocculants (LBF) were tested for their ability to improve the biosludge dewaterability based on Capillary Suction Time (CST) and dry cake solids achieved with a Crown Press. The results demonstrate that LBFs alone can significantly enhance dewatering with a decrease in CSTs from 72.7 ± 5.1 s (unconditioned biosludge) to 23.3 ± 0.4 s and an increase in dry cake solids after pressing from 7.1 ± 0.5% to 13.9 ± 1.3% with a relatively high dosage of 7.5% w/w. However, with dual conditioning a LBF and 0.1% w/w anionic polyacrylamide (APAM), the required dosage of LBF was reduced to 3% w/w to achieve a dry cake solids content of 13.8 ± 0.4%, the same as that achieved with Zetag8165, a commercial synthetic polymer. LBF addition lowered the particle surface charge, allowing the particles to agglomerate and enhancing for the biosludge dewaterability. The application of LBFs for sludge dewatering offers novel considerable promise for providing more sustainable approaches by optimizing the use of lignin from different extraction processes, applying various types of lignin modifications in combination with anionic polymers, and exploring different methods of disposal or utilization of the dewatered sludge. Highlights: Lignin based flocculants (LBFs) improved the dewaterability of biosludge. LBFs reduced the capillary suction time (CST) and increased dry solids after mechanical dewatering. LBF demand was significantly decreased through dual conditioning with anionic polymer. Charge neutralization and aggregation of particles are suggested as flocculation mechanisms.